Increasing the value added of production citronella oil and carrageenan in Rungkut Barata Surabaya - Dwi Yuli Pujiastuti; Laksmi Sulmartiwi; Ahmad Shofy Mubarak (OJS Universitas Muhammadiyah Gresik, 2021)
In this PKM program, our partner is residents in Rungkut Barata, Surabaya, East Java Province. This community has generated the production of citronella oil. However, the product only in the form of citronella oil in a simple package. Citronella oil from the refining process is one of the jobs for the people in Rungkut Barata where to improve welfare, a product diversification process is necessary. Seaweed is forms of algae that grow in the sea and has the biological activity for health. Carrageenan is the product result of seaweed extraction that have several function as thickener, emulsifier, suspension, and stabilizer. The pharmaceutical industry uses carrageenan for the manufacture of drugs, syrups, tablets, toothpaste, and shampoo. The cosmetics industry uses it as a gelling agent or binding agent. Based on interviews and observations in the field, there are 2 main focuses of the problems currently faced by partners, namely: 1) lack of knowledge about non-consumption seaweed and 2) product diversification of seaweed and citronella oil which have an added value. Some of the things planned by the PKM team are innovating citronella oil to be aromatic soap as well as providing training and mentoring for financial analysis, soap packaging and marketing. The purpose of this activity is to transfer knowledge of making soap, develop the creativity of the partner, increase the soap production and improve the welfare of the partner. This activity was realized with an approach in the form of making a sustainable cooperation program until the end of PKM, creating a family atmosphere between the two and understanding that the problems experienced were a shared problem so that they could be solved together according to the level of responsibility to achieve the expected benefits, namely increased yields, production and productivity and competitiveness, independence and welfare of the community.